theory of generalized diffusion on suspended sediment transport in the flows with mobile bed - Diep, Nguyen Van; Chung, Dang Huu (Vietnam Journal of Mechanics, 1990)
In this work the authors have used the theory of generalized diffusion to establish the one and two-dimensional models describing suspended sediment transport in the flows with mobile bed. Here the exchange between suspended sediment and bed-load is taken into account. The set of equations obtained is closed by using the known experiment formulas.